2012
DOI: 10.1371/journal.pone.0051746
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Directly Sequesters Adipocytic and Insulin Sensitizing Activities but Not Osteoblastic Activity of PPARγ2 in Marrow Mesenchymal Stem Cells

Abstract: Lineage allocation of the marrow mesenchymal stem cells (MSCs) to osteoblasts and adipocytes is dependent on both Wnt signaling and PPARγ2 activity. Activation of PPARγ2, an essential regulator of energy metabolism and insulin sensitivity, stimulates adipocyte and suppresses osteoblast differentiation and bone formation, and correlates with decreased bone mass and increased fracture rate. In contrast, activation of Wnt signaling promotes osteoblast differentiation, augments bone accrual and reduces total body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 51 publications
(86 reference statements)
2
26
0
Order By: Relevance
“…In addition, Petrie et al [32,33] reported that S1P or FTY720 improved the osseous tissue growth in vivo. Cawthorn et al [4] and Rahman et al [5] showed that the Wnt/b-catenin signaling pathway regulated not only the inhibition of adipogenesis, but also the stimulation of osteoblastogenesis in MSC. Although the involvement of Wnt in S1P-modulated MSC differentiation remains unclear, our understanding of the mechanism of S1P for MSC differentiation is important for bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Petrie et al [32,33] reported that S1P or FTY720 improved the osseous tissue growth in vivo. Cawthorn et al [4] and Rahman et al [5] showed that the Wnt/b-catenin signaling pathway regulated not only the inhibition of adipogenesis, but also the stimulation of osteoblastogenesis in MSC. Although the involvement of Wnt in S1P-modulated MSC differentiation remains unclear, our understanding of the mechanism of S1P for MSC differentiation is important for bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the reduction of cAMP by S1P triggered the inhibition of adipogenic differentiation of C3H10T1/2 cells, we further examined the effect of S1P on cAMPindependent adipogenic differentiation by rosiglitazone, a directional PPARc agonist [5]. Since C/EBPb is the upstream gene of PPARc, rosiglitazone did not increase C/EBPb mRNA and protein levels, and S1P did not influence their levels, compared to adipogenic differentiation cocktail (Fig.…”
Section: S1p Does Not Affect Camp-independent Adipogenic Differentiationmentioning
confidence: 92%
See 1 more Smart Citation
“…Rosiglitazone forces MSCs toward the adipogenic lineage and blocks osteogenesis, in part by increasing β-catenin degradation, leading to enhanced marrow adiposity and bone loss [5759]. This has led to the tenet that there must be exclusive commitment toward one cell type over another.…”
Section: Molecular and Metabolic Determinants Of Adipogenesis And mentioning
confidence: 99%
“…The lineage commitment can be triggered by environmental cues consisting of BMP and Wnt signaling for osteoblast and fatty acids and hormonal stimulation for adipocytes resulting in transcriptional upregulation of two key proteins: the runt-related transcription factor 2/core-binding factor-α1 (RUNX2/CBFA1; also known as AML3 and PEBP2αA) and the peroxisome proliferator-activated receptor gamma2 (PPARγ2 or NR1C3) [2]. Reciprocal regulation of expression of these two transcription factors includes the activity of Wnt signaling which upregulates RUNX2 and suppresses PPARγ2, and suppressive effect of PPARγ2 on Wnt signaling activity and RUNX2 expression [3, 4, 2]. An additional mechanism which operates at the level of activity of both proteins includes TAZ (transcriptional coactivator with PDZ-binding motif) which co-activates RUNX2-dependent gene transcription while repressing PPARγ-dependent gene transcription [5].…”
Section: Introductionmentioning
confidence: 99%